1995
DOI: 10.1524/ract.1995.68.3.161
|View full text |Cite
|
Sign up to set email alerts
|

Separation of 111Ag from Neutron Irradiated Natural Palladium

Abstract: Palladium and silver ( lu Ag) are sorbed as complex amine cations on AG 50W-X8 cation exchanger. " 1 Ag is selectively eluted with 0.5 Μ NaCl solution. >85% 1 "Ag is recovered with <1 μg/ml palladium as an impurity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Similarly, a 109 Cd/ 109m Ag generator was developed, based on the sorption of Cd on AG 50W-X8 organic cation exchanger [40]. 111 Ag [41] and 109m Ag [42] were selectively eluted from various matrices. 111 Ag was also produced and separated by irradiating palladium [43].…”
Section: Improvements In Radionuclide Production Methodsmentioning
confidence: 99%
“…Similarly, a 109 Cd/ 109m Ag generator was developed, based on the sorption of Cd on AG 50W-X8 organic cation exchanger [40]. 111 Ag [41] and 109m Ag [42] were selectively eluted from various matrices. 111 Ag was also produced and separated by irradiating palladium [43].…”
Section: Improvements In Radionuclide Production Methodsmentioning
confidence: 99%
“…Cation Exchange: Mansur et al reported a cation-exchange-based chromatographic separation of 111 Ag from the neutron-irradiated Pd matrix [ 21 ]. According to their protocol, the Pd target (100 mg) was dissolved in aqua regia (5 mL), followed by evaporation to dryness [ 21 ]. The process was repeated by adding HCl to remove residual amounts of HNO 3 and the bulk was dissolved in distilled water (10 mL).…”
Section: Separation Of Silver Radioisotopesmentioning
confidence: 99%
“…The use of antibodies labeled with various radionuclides to deliver therapeutic doses of radiation for human cancer treatment has now been shown to give clinically significant effects in a number of studies [93]. Such radioimminotherapy (RAIT) is dependent on several contributing factors including the radiosensitivity of the target tumor, the characteristic of the chosen antibody and, of course, the nature of the nuclide employed [94]. The carrier-free 111 Ag isotope has been suggested to be more suitable for RAIT than the commonly used 131 I, on the basis of its good β-emission properties, appropriate half-life of 7.5 days and much more favourable γ-ray component (342 keV, 6% for 111 Ag compared with 363 keV, 82% for 131 I) [95].…”
Section: Radioisotopes Of Silvermentioning
confidence: 99%